GEN Z ENTREPRENEURIAL INTENTIONS : ROLE OF KNOWLEDGE, MOTIVATION, AND SELF CONFIDENCE - Nailatus Sadiyah; Nihayatu Aslamatis Solekah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The development of global entrepreneurship shows a positive trend, as indicated by the increasing contribution of MSMEs to the economy. Generation Z, who grew up in the digital era, has characteristics that are adaptive to technology, innovative, and care about social values, so they have high potential in the world of entrepreneurship. This study aims to analyze the influence of motivation, entrepreneurial knowledge, and self-confidence on Gen Z's intention in entrepreneurship in Malang City. The method used is quantitative by distributing online questionnaires to 157 students from various universities in Malang City, who were selected through purposive sampling techniques. The data were analyzed using multiple linear regression preceded by validity, reliability, and classical assumption tests, and processed using SPSS. The results of the t-test show that partially, the three independent variables, namely motivation, entrepreneurial knowledge, and self-confidence, have a significant effect on intention in entrepreneurship. The F test also strengthens these results, where simultaneously the three variables have a significant effect on Gen Z's intention in entrepreneurship. This finding confirms the importance of the role of these three factors in encouraging the younger generation to become entrepreneurs in the modern era.